Genetic Types of the tp12cx Strike-Slip Fault Segments and Their Role in Controlling Reservoirs in the Tarim Basin - Lv, Yanping; Ma, Hailong; Wang, Zhen; Deng, Guangxiao; Wen, Huan (Frontiers in Earth Science, 2022)
Based on high-precision 3D seismic data and the principle of structural analysis, this paper defines the structural evolution characteristics of the tp12cx strike-slip fault in the key structural period and identifies the fault segmentation types. Combined with the statistical results of drilling production data and fault width, it is confirmed that there is a corresponding reservoir model. The tp12cx strike-slip fault experienced two tectonic activity phases controlling reservoir development: the middle Caledonian and the late Caledonian to early Hercynian. In the middle Caledonian period, a left-lateral and left-step strike-slip fault was formed. The overlapping segments of the left steps were extension zones, and the rest were linear translation segments. From the late Caledonian to the early Hercynian, the movement mode changed from left-lateral to right-lateral, and the arrangement of left steps remained unchanged, forming right-lateral and left-step strike-slip faults. That is, as a weak zone, the extension zones of all the preexisting overlapping segments took the lead in moving into many translation segments and maintained the pull apart property. During the right-lateral slipping process of all the original linear translation segments along the fault, they were blocked and squeezed by the surrounding rocks on both sides, forming a series of "positive" flower-shaped fault anticlines, which became overlapping segments, and the fault property became compressive. Under the continuous action of the right-lateral slipping, a regional right-lateral and right-step strike slip fault formed. The interiors of the right-step-arranged faults were composed of the left-step arranged faults. Among them, the right-step overlapping segments were weakly pulled apart, the fault width of the internal left-step translation and overlapping segments became wider, and the dissolution became stronger. The deformation of the right-step translation segments was weak and basically maintained the characteristics of the previous stage. According to the evolution and superposition of translational and overlapped segments and the changes in fault properties, four types of strike-slip fault segments and corresponding reservoir models are divided. The fault width and output of type II and type IV with pull-apart properties are much larger than those of type I and type III with compressive properties.